2021
DOI: 10.1113/jp281773
|View full text |Cite
|
Sign up to set email alerts
|

Delayed KCNQ1/KCNE1 assembly on the cell surface helps IKs fulfil its function as a repolarization reserve in the heart

Abstract: In adult ventricular myocytes, the slow delayed rectifier (I Ks ) channels are distributed on the surface sarcolemma, not t-tubules.r In adult ventricular myocytes, KCNQ1 and KCNE1 have distinct cell surface and cytoplasmic pools.r KCNQ1 and KCNE1 traffic from the endoplasmic reticulum to the plasma membrane by separate routes, and assemble into I Ks channels on the cell surface.r Liquid chromatography/tandem mass spectrometry applied to affinity-purified KCNQ1 and KCNE1 interacting proteins reveals novel inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The Kv7.1 channel routes to the cell surface by an unconventional mechanism – bypassing the Golgi apparatus – which drives the channel via ER‐PMjs to the cell membrane 7,8 . Thus, Brefeldin, which suppresses the canonical Golgi‐dependent anterograde route, did not alter Kv7.1 ER localization (Figure S2A,B).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The Kv7.1 channel routes to the cell surface by an unconventional mechanism – bypassing the Golgi apparatus – which drives the channel via ER‐PMjs to the cell membrane 7,8 . Thus, Brefeldin, which suppresses the canonical Golgi‐dependent anterograde route, did not alter Kv7.1 ER localization (Figure S2A,B).…”
Section: Resultsmentioning
confidence: 98%
“…This K + current is crucial for the termination of cardiac action potentials. The association takes place in ER‐PMjs before translocation to the plasma membrane 7,8 . Thus, the I Ks channel, expressed in the sarcolemma as well as its contact sites with the SR, is located in the characteristic T‐tubule structures, which house the ion channel machinery for excitation‐contraction (E‐C) coupling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of biotin outcompetes the SBP/streptavidin interaction and severs the connection between the hook and bait allowing the protein to be released into the secretory pathway. This system has recently been used to study glutamate receptor [151], KCNQ1/KCNE1 [152], and to study altered transport kinetics during pathological conditions [153]. One could envisage that this system could be used to determine when and where the various auxiliary subunits of the channel join the α1 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, real-time study of channel and partner (co-)trafficking should help understand whether interactions with and/or competition between different channel partners during intracellular trafficking steps direct the final destination of ion channels. Recently, using cutting-edge live-imaging technologies, the group of Tseng showed that KCNQ1 and KCNE1 traffic through separate routes and only assemble at the sarcolemma to form I Ks [ 35 ]. Furthermore, to understand the development of arrhythmias associated upstream or downstream of myocardial remodeling, the question of the interplay between electrical and structural polarization must be addressed.…”
Section: The Trafficking Machinery Of Cardiomyocytesmentioning
confidence: 99%